Management of Phenytoin Induced Gingival Overgrowth: A Case Report (Journal of Orofacial Research, 2021)
Gingival hyperplasia/ hypertrophy/ overgrowth are common terms used to describe any type of enlargement of gingiva. Thisovergrowth can be associated with various etiological reasons. Accordingly, it has been classified into different subheads. Thiscan either be localised or generalised, papillary, or marginal depending on the area affected and diffuse or discrete. Inflammatoryenlargements can be acute or chronic. Factors may range from inflammation due to local biofilm to neoplastic enlargements.Studies have also attributed gingival overgrowth to be associated with certain drugs (anticonvulsants, immunosuppressants andcalcium channel blockers). This case report narrates the management of phenytoin induced gingival overgrowth using externalbevel gingivectomy to achieve desirable esthetics.